(untitled) (JURNAL GEOGRAFI, 2025)
River water quality in urban areas, particularly in Yogyakarta, has declined due to pollution from domestic, industrial, and agricultural activities. Communal wastewater treatment plants (CWWTPs) were established to address this issue; however, they have not been operating optimally, limiting their impact on improving water quality. Therefore, this study aims to 1) analyze the condition of water quality temporally and spatially in river sections in Yogyakarta City, 2) determine river water quality index temporally and spatially using Canadian Council of Ministers of the Environmental (CCME) method and Biodegradability Index (BI), 3) evaluate the level of water pollution between CCME method and BI, and 4) analyze water quality parameters influencing the pollution level. The study procedures were carried out using the institutional survey method, and data were obtained from temporal water quality monitoring by Yogyakarta City Environmental Service. Water quality assessment was based on standards according to Governor Regulation No. 20 of 2008. Evaluation of pollution levels was carried out using water quality index with CCME method and BI. The influence of dominant parameters was statistically tested using Principal Component Analysis (PCA). The results showed that water quality in Yogyakarta City based on CCME method and BI was dominated by the poor and non-biodegradable categories. Between 2020 and 2023, the CCME and BI index values of rivers showed an increasing trend, indicating a reduction in pollution. The primary factors affecting water quality include NO₂, TDS, temperature, DO, NO₃, and total phosphate, originating from domestic and agricultural activities. In contrast, Cu, Zn, and Cd are primarily sourced from industrial activities.